Analisis Proporsi Anggaran Belanja Pembangunan Dan Anggaran Belanja Rutin Terhadap Pertumbuhan Ekonomi Kabupaten Lombok Tengah Tahun 2012-2016 - Fatimah, Siti (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2018)
In the line with the flow of authority which more widely owned by every region in this era of regional autonomy so the rule and function of the regional incometrough the extracting potential of each region become a very important , the perspective regional autonomy which is related with the economic growth could be seen from many aspect such as development expenditure allocation , routine expenditure allocation and other expenditures, the research aim is to find out the effect of development expenditure and routine expenditure toward PDRB growth rate in central Lombok district year of 2012-2016, the proposed hypothesis is suspected that development expenditure and routine expenditure have an effect toward the growth rate in central Lombok district year of 2012-2016 which relatively is not too significant , this is descriptive research , data collecting technique use library study and field research variable done by regional income (PD), locally generated revenue (PAD) apparatus expenditure (BA), public expenditure (BP), regional expenditure (BD) , regional revenue and expenditure budget (APBD) ,product domestic regional bruto (PDRB), while analysis model use development budget proportions toward economic regional growth and routine expenditure ratio on economic regional growth also growth analysis contribution of each expenditure either development expenditure or routine expenditure, research result shows the average growth rate for five years since 2012-2016 that the growth development expenditure contribution toward PDRB growth in central Lombok district is 11,79 % while for routine expenditure for five years since 2012-2016 the contribution growth rate toward PDRB growth rate in central Lombok district is 7,50 % that smaller compared with development expenditure contribution which means is not significant.